Top earnings inequality and the gender pay gap: Canada, Sweden and the United Kingdom - Fortin, Nicole M.; Bell, Brian; Böhm, Michael Johannes (Bonn, 2017)
"This paper explores the consequences of the under-representation of women in top jobs for the overall gender pay gap. Using administrative annual earnings data from Canada, Sweden, and the United Kingdom, it applies the approach used in the analysis of earnings inequality in top incomes, as well as reweighting techniques, to the analysis of the gender pay gap. The analysis is supplemented by classic O-B decompositions of hourly wages using data from the Canadian and U.K. Labour Force Surveys. The paper finds that recent increases in top earnings led to substantial "swimming upstream" effects, therefore accounting for differential progress in the gender pay gap across time periods and a growing share of the gap unexplained by traditional factors."